Baseline glucose-to-lymphocyte ratio predicts nivolumab outcomes in advanced non-small cell lung cancer: a multicenter retrospective study - Ersoy, Mustafa; Kefeli, Umut; Cabuk, Devrim; Bayram, Ertugrul; Bayir, Duygu; Bozkurt, Oktay; Ürün, Muslih; Coşar, Ramazan; Sakalar, Teoman; Mutlu, Emel; Cengiz, Muhammet; Sahin, Elif; et al. (Frontiers in Immunology, 2026)
BackgroundBiomarkers guiding immunotherapy in non-small cell lung cancer (NSCLC) are limited. The glucose-to-lymphocyte ratio (GLR), integrating metabolic and immune status, has shown prognostic value in several cancers but has not been systematically evaluated in patients receiving PD-1 blockade.MethodsWe retrospectively analyzed 837 patients with advanced or metastatic NSCLC treated with nivolumab across 21 oncology centers in Turkey (2015–2025). Baseline GLR was calculated from fasting glucose and absolute lymphocyte counts. Overall survival (OS) and progression-free survival (PFS) were estimated using Kaplan–Meier and compared with log-rank tests. Multivariate Cox regression models identified independent predictors. Receiver operating characteristic (ROC) analysis determined the optimal GLR cut-off for OS, which was subsequently applied to PFS analyses for consistency.ResultsThe optimal GLR cut-off for mortality was ≥70.76 (AUC = 0.635, 95% CI: 0.597–0.674; p < 0.001). Patients with GLR <70.76 achieved significantly longer OS (median 24.1 vs 9.6 months; p < 0.001) and PFS (9.7 vs 5.8 months; p < 0.001) compared with those with GLR ≥70.76. In multivariate analysis, high GLR and poor ECOG performance status independently predicted worse OS. Prior thoracic radiotherapy was associated with improved outcomes.ConclusionBaseline GLR is a practical, cost-effective biomarker that independently predicts OS in advanced NSCLC patients treated with nivolumab. Elevated GLR likely reflects metabolic dysfunction and impaired immune reserve, both unfavorable for PD-1 blockade efficacy. Prospective studies are warranted to validate GLR and define its role in clinical decision-making.